Reducing to First-Order Equation

  • Thread starter Banana
  • Start date
  • #1
25
0
Can someone double check me please? I'm not sure if it matters that the fourth and first orders are missing.

Reduce to a first-order equation:

2y''''' + 12x^3y''' - 2y^7y'' - 8y = 0

My solution:
u1' = u2
u2' = u3
u3' = u4
u4' = u5
u5' = -6x^3(u4) + y^7(u3) + 4(u1)
 

Answers and Replies

  • #2
Clausius2
Science Advisor
Gold Member
1,435
5
I think it's correct. First and fourth order do not appear because in original equation don't appear too.
 

Related Threads on Reducing to First-Order Equation

Replies
3
Views
2K
  • Last Post
Replies
2
Views
3K
  • Last Post
Replies
2
Views
2K
Replies
4
Views
931
  • Last Post
Replies
18
Views
4K
Replies
1
Views
1K
Replies
4
Views
1K
Replies
3
Views
1K
Replies
6
Views
853
Replies
4
Views
3K
Top